Pengaruh Budaya Kerja dan Konflik Kerja terhadap Kinerja Pegawai di Puskesmas Sukorambi Kabupaten Jember - Devi Alfia; Nursyamsida Tohari; Yusita Titi Hapsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of work culture and work conflict on employee performance at the Sukorambi Community Health Center in Jember Regency. The research method used was quantitative research with an explanatory research design. The study population consisted of 70 employees, and the entire population was sampled using a total sampling technique. Data were collected through a Likert-scale questionnaire distributed using Google Forms. Data were then analyzed using the Pearson correlation test and multiple linear regression with SPSS. The results showed that work culture had a positive and significant relationship with employee performance (r = 0.738; p = 0.000), while work conflict had no significant relationship with employee performance (r = -0.006; p = 0.958). The regression results showed that work culture had a positive and significant effect on employee performance (β = 0.245; p = 0.000), while work conflict had a negative and significant effect on employee performance (β = -0.119; p = 0.000). Simultaneously, work culture and work conflict explained 55.5% of the variation in employee performance (R² = 0.555). The conclusion of this study indicates that a strong work culture can improve employee performance, while poorly managed work conflict can decrease it. Therefore, strengthening work culture and effective conflict management are important factors in improving employee performance at the Sukorambi Community Health Center in Jember Regency. Keywords: Work Culture, Employee Performance, Work Conflict, Employees, Community Health Center